2021
DOI: 10.1080/21655979.2021.1972082
|View full text |Cite
|
Sign up to set email alerts
|

The anti-tumor effects of evodiamine on oral squamous cell carcinoma (OSCC) through regulating advanced glycation end products (AGE) / receptor for advanced glycation end products (RAGE) pathway

Abstract: Sun (2021) The anti-tumor effects of evodiamine on oral squamous cell carcinoma (OSCC) through regulating advanced glycation end products (AGE) / receptor for advanced glycation end products (RAGE) pathway, Bioengineered, 12:1, 5985-5995,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…[43][44][45] Regarding OSCC, there have been several investigations that aimed to evaluate the role and expression of RAGE receptor. [46][47][48] In a study that evaluated 74 OSCC samples, the RAGE receptor was reported to be a prognostic factor, and was significantly associated with the depth of invasion and local recurrence. 46 Moreover, a particular role of RAGE in OSCC pathogenesis was confirmed in an in vitro study, where this receptor proved to be activated in a paracrine manner by the extracellular molecule high-mobility group box 1 (HMGB1) that was secreted by the OSCC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[43][44][45] Regarding OSCC, there have been several investigations that aimed to evaluate the role and expression of RAGE receptor. [46][47][48] In a study that evaluated 74 OSCC samples, the RAGE receptor was reported to be a prognostic factor, and was significantly associated with the depth of invasion and local recurrence. 46 Moreover, a particular role of RAGE in OSCC pathogenesis was confirmed in an in vitro study, where this receptor proved to be activated in a paracrine manner by the extracellular molecule high-mobility group box 1 (HMGB1) that was secreted by the OSCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…47 Furthermore, RAGE proved to be significantly decreased by evodiamine, a novel anti-tumor drug, inhibiting proliferation, invasion and angiogenesis of OSCC both in vitro and in vivo. 48 Finally, the gene that encodes the RAGE receptor is predicted to be one of the hsa-miR-769-5p targets both in CDS and 5ʹUTR positions, according to the miRWalk v. 3.0 database. 19 Finally, for hsa-miR-4500, there is no evidence so far concerning its expression in OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis was investigated by tube formation analysis according to a previous report [ 23 ]. In brief, HUVEC cells (1 × 10 4 /well) were added in Matrigel-coated 96-well plates overnight.…”
Section: Methodsmentioning
confidence: 99%
“…The interaction between IGF2BP2 and HPSE was analyzed by luciferase reporter analysis referring to a previous report with some modifications [ 23 ]. In brief, the WT or MUT sequence of HPSE 3ʹ untranslated region (UTR) with IGF2BP2 binding sites was inserted in the psi-CHECK2 vector (Promega), generating the WT and MUT HPSE luciferase reporter vectors.…”
Section: Methodsmentioning
confidence: 99%
“…4 Evodiamine, a natural indole alkaloid extracted from the Evodia ruticarpa plant, has demonstrated potent anticancer activity against a range of tumors. 5 It exhibits topoisomerase inhibition 6 and has been shown to impact tumor characteristics like apoptosis, 7 cell proliferation, 8 invasion, migration, 9,10 and so forth. Metabolic reprogramming is a hallmark of tumorigenesis, 11 encompassing alterations in processes like aerobic glycolysis, the citric acid cycle, one-carbon metabolism, and lipid metabolism.…”
mentioning
confidence: 99%